OBTENÇÃO, CARACTERIZAÇÃO E AVALIAÇÃO DA CITOTOXICIDADE DE NANOPARTÍCULAS DE POLI (ÁCIDO LÁCTICO) CONTENDO TAMOXIFENO E CURCUMINA - DALPOSSO, LORIANGELA MARCELI (2015)
Tamoxifen and curcumin are compounds widely studied for the treatment of cancer, tamoxifen is already used in breast cancer, but it has several side effects. Many studies report the activity of curcumin in cancer, but it has low bioavailability. Therefore, the combination of these compounds and encapsulation in nanoparticles are promising strategy for the treatment of cancer, which can increase the antitumor activity, reduce side effects of tamoxifen and increase the bioavailability of curcumin, as well as providing a controlled release. In this study poly (lactic acid) nanoparticles containing curcumin, tamoxifen citrate (CTAM) and the combination of these compounds were obtained by the method of emulsification-solvent evaporation (O/W). To calculate the encapsulation efficiency an analytical method by high performance liquid chromatography to quantify curcumin and CTAM at the same time was developed, this method was validated and showed linearity, specificity, precision, accuracy and robustness. The encapsulation efficiency was similar for curcumin and CTAM when encapsulated together or alone, with approximately 57% for CTAM and 92% for curcumin. The nanoparticles had spherical morphology, with a size next to 190 nm, the zeta potential was -16 mV to CTAM nanoparticles, -26 mV to curcumin nanoparticles and -17 mV for curcumin-CTAM nanoparticles. The size, zeta potential and polydispersity index were stable for 90 days. The nanoparticles obtained were also analyzed by infrared spectroscopy, differential scanning calorimetry and thermogravimetry. The in vitro release in 120 hours was 57% for curcumin and 49% for CTAM in curcumin-CTAM nanoparticle, 45% for CTAM nanoparticle and 61% for curcumin nanoparticles. Evaluating the cytotoxic activity against red blood cells, it was observed a decrease in hemolysis of CTAM when associated with curcumin, when encapsulated both compounds showed low hemolysis in 96 hours, while the drug in free form showed 100% hemolysis in 24 hours. In the cytotoxicity against melanoma cells (B16-F10) nanoparticles containing curcumin-CTAM showed an additive effect compared to the nanoparticles of the isolated compounds.